The effect of prior knowledge and intelligibility on the cortical entrainment response to speech - Baltzell, Lucas S. (J Neurophysiol, 2017)
It has been suggested that cortical entrainment plays an important role in speech perception by helping to parse the acoustic stimulus into discrete linguistic units. However, the question of whether the entrainment response to speech depends on the intelligibility of the stimulus remains open. Studies addressing this question of intelligibility have, for the most part, significantly distorted the acoustic properties of the stimulus to degrade the intelligibility of the speech stimulus, making it difficult to compare across “intelligible” and “unintelligible” conditions. To avoid these acoustic confounds, we used priming to manipulate the intelligibility of vocoded speech. We used EEG to measure the entrainment response to vocoded target sentences that are preceded by natural speech (nonvocoded) prime sentences that are either valid (match the target) or invalid (do not match the target). For unintelligible speech, valid primes have the effect of restoring intelligibility. We compared the effect of priming on the entrainment response for both 3-channel (unintelligible) and 16-channel (intelligible) speech. We observed a main effect of priming, suggesting that the entrainment response depends on prior knowledge, but not a main effect of vocoding (16 channels vs. 3 channels). Furthermore, we found no difference in the effect of priming on the entrainment response to 3-channel and 16-channel vocoded speech, suggesting that for vocoded speech, entrainment response does not depend on intelligibility. NEW & NOTEWORTHY Neural oscillations have been implicated in the parsing of speech into discrete, hierarchically organized units. Our data suggest that these oscillations track the acoustic envelope rather than more abstract linguistic properties of the speech stimulus. Our data also suggest that prior experience with the stimulus allows these oscillations to better track the stimulus envelope.